2009
DOI: 10.1111/j.1420-9101.2009.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that high levels of inbreeding depress sperm competitiveness

Abstract: The effects of inbreeding on sperm quantity and quality are among the most dramatic examples of inbreeding depression. The extent to which inbreeding depression results in decreased fertilization success of a male’s sperm, however, remains largely unknown. This task is made more difficult by the fact that other factors, such as cryptic female choice, male sperm allocation and mating order, can also drive patterns of paternity. Here, we use artificial insemination to eliminate these extraneous sources of variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 50 publications
9
95
1
Order By: Relevance
“…2006; Zajitschek et al. 2009). In birds, wide interspecific variation in levels of sexual promiscuity has been documented (Griffith et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Zajitschek et al. 2009). In birds, wide interspecific variation in levels of sexual promiscuity has been documented (Griffith et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with studies on invertebrates and plants, most such studies have not used controlled breeding designs (e.g., full‐sib mating) to produce inbred and outbred individuals raised under standard conditions (but see Zajitschek et al. 2009; Mehlis et al. 2012; Gasparini et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our result is in agreement with the previous work on a feral (Australian) guppy population, in which significant inbreeding depression in sperm production was found after two generations of full-sib matings (Zajitschek and Brooks 2010). Another study on the same guppy population revealed that sperm competitiveness is reduced only after four generations of full-sib mating when the number of sperm inseminated is experimentally controlled for using artificial insemination (Zajitschek et al 2009). These two results indirectly suggest that the pattern of directional selection for sperm number and velocity may be similar in our and in the Australian population studied by Zajitschek and colleagues (although sperm quality has not been directly measured in the latter).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fact that captive breeding practices increase the risk of inbreeding suggests that potential decline in sperm quality may be directly related to inbreeding depression. Supporting this view, the detrimental effects of inbreeding on semen traits have been well demonstrated: It reduces the ejaculate volume, number of motile sperm and/or number of normal sperm (Roldan et al 1998;Gomendio et al 2000;van Eldik et al 2006;Gage et al 2006;Fitzpatrick and Evans 2009;Zajitschek et al 2009). However, selection and inbreeding often have opposite effects on fitness-related traits, and it has been demonstrated that selection can delay or hinder the detrimental effects of inbreeding (Connor and Bellucci 1979;Wade et al 1996).…”
mentioning
confidence: 94%
“…Inbreeding has severe effects on individual fitness (e.g. Hedrick and Kalinowski 2000;Drayton et al 2007) and traits that are closely related to reproduction (Zajitschek et al 2009). In addition to the loss of genetic diversity, captive breeding may also cause selective changes in various phenotypic traits (e.g.…”
mentioning
confidence: 99%